Percutaneous N-Butyl-Cyanoacrylate Embolization for Treating Ruptured Pancreaticoduodenal Aneurysm: A Case Report - Joo Yeon Jang; Jin Hyeok Kim; Tae Un Kim; Hwaseong Ryu; Tae Beom Lee; Je Ho Ryu; Ung Bae Jeon (Medicina, 2022)
Background and Objectives: Pancreaticoduodenal artery aneurysms are rare visceral artery aneurysms. Interventional treatments, including transcatheter embolization, have an acceptable success rate. We report a case of ruptured pancreaticoduodenal aneurysm that was successfully treated with percutaneous N-Butyl-cyanoacrylate (NBCA) embolization after failed transcatheter embolization. Materials and Methods: A 53-year-old man presented to the emergency department with abdominal pain. Computed tomography (CT) revealed a ruptured aneurysm in the inferior pancreaticoduodenal artery (IPDA) with retrohemoperitoneum. The patient underwent percutaneous NBCA embolization after transcatheter embolization failure. Results: On CT, the pancreaticoduodenal aneurysm was completely embolized. No additional bleeding events occurred. Conclusions: Percutaneous NBCA embolization is safe and effective for treating patients with ruptured pancreaticoduodenal aneurysms after failed transcatheter embolization.